The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1099/00207713-49-4-1891
|View full text |Cite
|
Sign up to set email alerts
|

Carnobacterium inhibens sp. nov., isolated from the intestine of Atlantic salmon (Salmo salar)

Abstract: Strain KIT, isolated from the gastrointestinal tract of Atlantic salmon (Salmo salar), has the capacity to inhibit the growth of the fish pathogens Vibrio anguillarum and Aeromonas salmonicida. Strain K I T is a motile Gram-positive psychrophilic rod that lacks both catalase and oxidase, which does not grow on acetate containing media, but grows at pH 9 and in TSB with up to 6 O/ O sodium chloride content. Strain K I T is facultatively anaerobic and tryptone as a sole source of nutrient promotes growth. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 19 publications
1
50
0
2
Order By: Relevance
“…3 Species of Carnobacterium are frequent inhabitants of the intestine, urogenital tracts, and gills of both fresh and salt water teleosts, in both aquaculture and in wild populations. 1,7,9,[15][16][17] These organisms can also be cultured from temperate and polar ocean waters, as well as certain terrestrial environments. 11,20 Some species of Carnobacterium are known to produce bacteriocins, proteins that kill or inhibit the growth of other bacteria, and this property has led to continuing interest and use of Carnobacterium species as probiotics in aquaculture and food preservation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Species of Carnobacterium are frequent inhabitants of the intestine, urogenital tracts, and gills of both fresh and salt water teleosts, in both aquaculture and in wild populations. 1,7,9,[15][16][17] These organisms can also be cultured from temperate and polar ocean waters, as well as certain terrestrial environments. 11,20 Some species of Carnobacterium are known to produce bacteriocins, proteins that kill or inhibit the growth of other bacteria, and this property has led to continuing interest and use of Carnobacterium species as probiotics in aquaculture and food preservation.…”
Section: Discussionmentioning
confidence: 99%
“…The five species isolated from foods, such as poultry, meat, sausage, cheese, and seafood, are Carnobacterium piscicola, C. divergens, C. mobile, C. gallinarum, and C. viridans (4,13,19,20,21,31,33,34). C. funditum and C. alterfunditum were isolated from anoxic Antarctic lake waters (15), while C. inhibens was isolated from the intestine of an Atlantic salmon (23). A Lactobacillus species, Lactobacillus maltaromicus, was found to be very similar to C. piscicola, and recently these two species have been considered synonymous (35).…”
mentioning
confidence: 99%
“…The positive control bacteria, C. inhibens which Jöborn et al [41] reported to display antagonistic effect against A. salmonicida, showed no sign of antagonism in the present study. This observation therefore indicates that antagonisitic activity of C. inhibens is only effective when cells are actively incubated together or that antagonistic extracellular products are only produced by C. inhibens in the presence of A. salmonicida.…”
Section: Discussionmentioning
confidence: 32%